OPTIMALISASI PERAN KODIM 0705/ MAGELANG DALAM PENANGGULANGAN BENCANA ALAM DI WILAYAH MAGELANG - Budi Mawardi Syam; Sobar Sutisna; Anwar Kurniadi; Kusuma Kusuma (Republic of Indonesia Defense University, 2023)
Several types of natural disasters have approached Magelang region throughout 2017 to 2022. The natural disasters are flash floods, landslides and strong winds. Under these conditions, it is necessary to involve Kodim 0705/Magelang in natural disaster management that occurs in the Magelang region in addition to BPBD and other agencies. This research aims to analyze the role of Kodim 0705/Magelang in assisting natural disaster management. This research used a qualitative method. Observation, interviews and literature studies are the methods used to collect research data. Data processing techniques used are data reduction, exposure of data obtained then drawing conclusions. The results showed that Kodim 0705/Magelang has an important and strategic role in natural disaster management in Magelang region. However, departing from the variation of disaster events, the development of science and technology and the dynamics that occur, steps are needed to optimize Kodim 0705/Magelang Role.